Environmental Innovation and Firm Performance in ASEAN-5 Countries: The Role of Board Tenure and Board Gender Diversity - Nahdia Haulah Rahmah; Sylvia Veronica Siregar (Jurnal Dinamika Akuntansi, 2026)
Purposes: This study seeks to assess impacts of environmental innovation on firm performance through a sustainability lens in the ASEAN-5 member states. This study analyzes the effects of envi- ronmental initiatives on financial performance as well as the moderating effects of board length and board gender diversity on this nexus. Methods: This research utilizes panel data from Refinitiv Eikon for the years 2019-2025 along with sustainability reports and employs panel regression. To assess the reliability of results, quadratic tests and robustness tests are employed. Firm performance is assessed through two main indicators: Tobin’s Q and ROA. Findings: As a result of this study, environmental innovation, especially in the case of innovation in circular activities, such as waste management, positively impacts financial and market performance. This study has also shown that board tenure does not have a moderating impact. In contrast, board gender diversity has a positive, moderating impact once the critical mass of women on the board has been reached. Novelty: This study seeks to merge board tenure and board gender diversity in the sustainability and corporate governance integration in the ASEAN-5 countries. Unlike predecessors that examined the impacts in isolation, this study analyzes board composition as a key governance element in the context of environmental innovation and performance of environmental innovation efforts.